PEREKAMAN KEHADIRAN KARYAWAN DENGAN AKSES GEOLOKASI: INOVASI SISTEM ABSENSI BERBASIS WEB: Employee Attendance Recording with Geolocation Access - Muhammad Rafli Nasution; Ahmad Fauzi (LPPM Universitas Abdurrab, 2024)
Employee attendance is one of the most crucial factors for an institution. There are various ways to address issues within an employee attendance system, and one of them is leveraging geolocation technology. Several studies investigate the controversies surrounding potential fraud and employee privacy threats when using geolocation access for attendance recording. Therefore, the system built in this research will prioritize utilizing geolocation access where location data during check-ins won’t be stored in the system, ensuring employee privacy remains intact. Moreover, this system will be designed to prevent employee fraud in manipulating locations. In its design, the system is constructed using the NEXT.JS framework and MySql as its database. Additionally, the research sample is drawn from two companies using an accidental sampling method as a data source. The result of this research is an attendance information system with web-based geolocation access that supports the attendance monitoring process within an institution. The development model used in this research is the RAD model, followed by using UML to document the system. Based on the final results obtained, a conclusion is drawn that this attendance system operates effectively, as evidenced by the conducted tests.